2012
DOI: 10.7555/jbr.26.20110132
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional structure prediction and proton nuclear magnetic resonance analysis of toxic pesticides in human blood plasma

Abstract: The purpose of this study was to investigate the nuclear magnetic resonance (NMR) assignments of hydrolyzed products extracted from human blood plasma. The correlations between chemical, functional and structural properties of highly toxic pesticides were investigated using the PreADME analysis. We observed that toxic pesticides possessed higher molecular weight and, more hydrogen bond donors and acceptors when compared with less toxic pesticides. The occurrence of functional groups and structural properties w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In terms of toxic effects, both of these compounds have the potential to become environmental toxins, but o-cumenol does not. According to Sharma et al [23] research, increasing functional groups causes increased toxicity. Idroxylgroup molecules are more responsive, which is an important identification throughout the process.…”
Section: Qsar Results For Isoprocarb and Metabolite Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of toxic effects, both of these compounds have the potential to become environmental toxins, but o-cumenol does not. According to Sharma et al [23] research, increasing functional groups causes increased toxicity. Idroxylgroup molecules are more responsive, which is an important identification throughout the process.…”
Section: Qsar Results For Isoprocarb and Metabolite Productsmentioning
confidence: 99%
“…Idroxylgroup molecules are more responsive, which is an important identification throughout the process. Sharma et al [23] identified hydrolysis as a dangerous insecticide.…”
Section: Qsar Results For Isoprocarb and Metabolite Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The band obtained at 1173.42/cm lies in the region 1260-1160/cm is due to P-O-C group. The positions of highly absorbed functional groups are mainly in the regions 2950-1190/cm that shows the characteristic of the number of adjacent hydrogen atoms in the molecular structure of malathion [ 35 ] .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a misleading image of food safety is produced, as at this dose level, the health impair is likely to occur in vivo [27,28]. It is estimated that over 900,000 people lose their life due to the ingestion of highly toxic pesticides [29]. For this reason, governments assign various rules to regulate the crop market retailing and food industry.…”
Section: Introductionmentioning
confidence: 99%